UV-curable fluoropolymers crosslinked with functional fluorescent dyes: the way to multifunctional thin-film luminescent solar concentrators. Issue 19 (26th April 2017) - Pintossi, Diego; Colombo, Alessia; Levi, Marinella; Dragonetti, Claudia; Turri, Stefano; Griffini, Gianmarco
Abstract : Co-crosslinking a luminescent dye with a photo-curable fluorinated polymer allows highly stable multifunctional thin-film luminescent solar concentrators to be obtained. Abstract : A novel photo-curable multifunctional luminescent system with high durability is presented in this work for application in thin-film luminescent solar concentrators (LSC), based on a fluorinated polymer matrix covalently linked to a newly synthesized functional perylene-derived luminescent organic dye. The UV-curable fluoropolymeric matrix consists of a blend of three different UV-curable fluorinated polymers. Such a matrix was co-reacted upon UV-light exposure with a suitably functionalized perylene-based luminescent organic dye bearing lateral carbon double bonds, to yield the solid crosslinked LSC thin film. A thorough characterization of the new luminescent system evidenced its excellent chemical, physical and optical properties, while its functional performance was evaluated in terms of LSC device response at varying dye concentrations. To assess the long-term stability of the new UV-curable LSC system, a long term (>800 h) light-exposure durability study was conducted on the LSC devices which fully retained their initial performance. In contrast, reference host/guest luminescent systems based on the same UV-curable fluoropolymeric matrix doped with a conventional fluorescent dye exhibited an overall ∼10% efficiency loss in the same time frame. In addition, such a novel UV-curable fluoropolymeric LSC system presented a highly hydrophobic character and moderate oleophobicity, which impart easy cleanability to the LSC coating, as a result of the highly perfluorinated nature of the polymeric matrix. This study represents the first demonstration of highly stable multifunctional UV-curable thin-film LSC systems and gives a clear demonstration of a straightforward room-temperature preparation process that may offer an easily scalable approach to highly stable and multifunctional LSC devices.